Comment on “casimir force in compact non-commutative extra dimensions and radius stabilization” - de Albuquerque, Luiz C. [UNESP]; Cavalcanti, Ricardo M. (Springer Nature, 2001)
We call attention to a series of mistakes in a paper by S. Nam recently published in this journal (J. High Energy Phys. 10 (2000) 044).
Keywords: Field Theories in Higher Dimensions; Non-Commutative Geometry